Isolation and Morphological Characterization of Colletotrichum spp. Associated with Mango Anthracnose in Mutoko District, Zimbabwe - Chabikwa , Nyarai; Chinheya, Cleopas C.; Mapope , Nyamande; Zivanai, Musabayana; Tembo, Lenon (Journal of Tropical Plant Protection, 2026)
Anthracnose is a fungal disease that severely affects mango (Mangifera indica L.) production globally. In Zimbabwe, mango production is a source of household nutrition and income from informal markets but there has been limited information on the fungal pathogens related to anthracnose in the main production areas. Lack of local baseline data limits proper diagnosis and the development of disease control measures. The main objective of this study was to morphologically characterize fungal isolates that were associated with anthracnose symptoms on mango fruits and leaves, which were collected from different orchards in the Mutoko District of Zimbabwe. Symptomatic samples from various trees were randomly collected in the different orchards. Pieces of tissue were taken from the edge of the lesions and surfaces sterilized, and were inoculation on potato dextrose agar. Colonies of the fungi that appeared were re-cultured to obtain pure culture. The isolates exhibited different colony morphology but mostly they produced grey to dark colonies of cottony to velvety textures. Based on morphology, the isolates were considered members of the Colletotrichum genus; nevertheless, species identification by molecular means was not performed. Through this research, the morphological characteristics of the anthracnose, associated Colletotrichum isolates from the Mutoko District were initially documented. This evidence calls for molecular and pathogenicity analyses to identify the species so that disease management can be effective.